'Viable but non‐culturable cells' are dead. (24th March 2021) - Song, Sooyeon; Wood, Thomas K.
Summary: Most bacteria lead lives of quiet desperation, so they sleep. By sleeping, bacteria survive ubiquitous stress, such as antibiotics, and can resuscitate to reconstitute infections. As for other nearly universal and highly regulated processes such as biofilm formation, in persistence, a small population of cells have an elegantly‐regulated pathway to become dormant. By inactivating their ribosomes, persister cells sleep through stress and resuscitate once (i) the stress is removed, (ii) nutrients are presented and (iii) ribosome content reaches a threshold. During stress, cells often become spheroid and die, becoming hollow, membrane‐enclosed vessels. How cellular content is lost is unclear, but it is obvious that these 'cell shells' are dead; i.e., 'There's no there there'. Critically, due to their intact membranes, the shells appear with membrane‐impenetrant stains as 'viable' particles. Unfortunately, the microbiology field of 'viable but non‐culturable cells' (VBNCs), though important for demonstrating the existence of dormant bacteria as a result of myriad stress states, has often mistaken these non‐viable shells as viable particles that mysteriously may be reborn, when an appropriate incantation is made. We argue here, based on experimental data, that if resuscitation occurs, it is the persister (always‐viable) cell population that revives, rather than the cell husks, which are dead.